Study on the Implementation of ILO Convention No. 98 in Indonesia and Its Comparison with Developed and Developing Countries - Nasution, Faizal Amir P; Tobing, Henriko; Farizal, Nur; Siregar, Syahdan Abdul Haris; Muhyiddin, Muhyiddin (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
Law No. 11 of 2020 on Job Creation has been reported by ITUC, KSPI, and KSBSI for violating ILO Convention No. 98. The Indonesian government is considered not involving Trade Unions/Labor Unions in terms of collective bargaining when drafting the Job Creation Law and the substance of the Job Creation Law which is considered to limit the role of Trade Unions/Labor Unions. The United States Government, the United States Labor Association, the Belgium Labor Association, Netherlands Labor Association, Republic of Korean Labor Association, and the Brazil Labor Association provide different views from Indonesia on the report. This study uses a qualitative approach supported by a literature study with FGD discussions. Based on the results of the study, reports by Trade Unions to the ILO regarding violations of ILO Convention No. 98 are generally still conjectural and do not depart from cases or violations of the law that have occurred. The government can report data on labor practices in Indonesia to show that there are no efforts to limit the role of Trade Unions/Labor Unions as evidence that the Government of Indonesia has implemented the principles in the ILO Convention. The government of Indonesia has an important role in increasing the provision of training and improving work competencies, increasing labor placement and expanding employment opportunities, as well as continuing to oversee the implementation of this Job Creation Law in companies and continuing to protect workers by providing legal protection and social security. The Government of Indonesia is currently receiving ILO Technical Assistance, and can propose to continue implementing the Job Creation Law regulations and continue to provide regular reports to the ILO. If this provision in practice is detrimental to workers and trade unions, then this provision can be challenged procedurally with the support of valid evidence.